2016
DOI: 10.3892/ijmm.2016.2837
|View full text |Cite
|
Sign up to set email alerts
|

Morin exerts cytoprotective effects against oxidative stress in C2C12 myoblasts via the upregulation of Nrf2-dependent HO-1 expression and the activation of the ERK pathway

Abstract: In the present study, we investigated the cytoprotective efficacy of morin, a natural flavonoid, against oxidative stress and elucidated the underlying mechanisms in C2C12 myoblasts. Our results indicated that morin treatment prior to hydrogen peroxide (H2O2) exposure significantly increased cell viability and prevented the generation of reactive oxygen species. H2O2-induced comet-like DNA formation and γH2AX phosphorylation were also markedly suppressed by morin with a parallel inhibition of apoptosis in C2C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 42 publications
3
12
0
1
Order By: Relevance
“…Prevention of I/R injury in organs has garnered much attention in recent years. Numerous studies have reported that some compounds can induce upregulation of the Nrf2/HO-1 pathway to exert protective effects on various I/R models (40)(41)(42)(43). The present study demonstrated that targeting the Nrf2/HO-1 pathway may provide a novel strategy for preventing hepatic I/R injury.…”
Section: Discussionsupporting
confidence: 56%
“…Prevention of I/R injury in organs has garnered much attention in recent years. Numerous studies have reported that some compounds can induce upregulation of the Nrf2/HO-1 pathway to exert protective effects on various I/R models (40)(41)(42)(43). The present study demonstrated that targeting the Nrf2/HO-1 pathway may provide a novel strategy for preventing hepatic I/R injury.…”
Section: Discussionsupporting
confidence: 56%
“…HO-1 is a target gene of Nrf2, which is involved in regulating cellular ROS production and scavenging (35,36). Activation of Nrf2-HO-1 signaling may alleviate myocardial I/R injury (37). In the present study, SIR treatment was observed to enhance the expression of Nrf2 in the nucleus and the whole cell, which may suggest increased nuclear translocation.…”
Section: Discussionsupporting
confidence: 52%
“…Morin exerts cytoprotective and genoprotective effects against oxidative stress. Morin treatment prior to H 2 O 2 exposure significantly prevented the generation of ROS, increased cell viability and prevented DNA damage by up-regulating Nrf2-dependent HO-1 expression through extracellular signal-regulated kinases (ERK) in C2C12 myoblasts [133]. In the case of myricetin, production of pro-inflammatory mediators through the suppression of signal transducer and activator of transcription 1 (STAT1) and Nuclear factor kappa-lightchain-enhancer of B cells (NF-kB) activation was inhibited by induction of Nrf2-mediated HO-1 expression in LPS-stimulated macrophages [134].…”
Section: Modulation Of Nrf2 Activity By Phenolic Compoundsmentioning
confidence: 99%